(untitled) (Berceo, 2024)
This article proposes an analysis of the correspondence exchanged between Baldomero Espartero and Luis Cutchet, both progressive liberals, especially after the former’s retreat to Logroño following the Progressive Biennium (1854-1856). It delves into the characters and their context, thus offering a structured interpretation along three lines: the politics of Espartero’s progressivism from opposition, the shaping of Espartero’s a self-perceptions, and the socio-political networks created around the Dukes of Victoria.